2017
DOI: 10.1080/0886022x.2017.1361840
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence on the use of anti-RAAS agents in congenital or acquired solitary kidney

Abstract: The conclusions of the few available studies on the topic are homogeneously in agreement with a long-term reno-protective activity of anti-RAAS drugs in patients with solitary kidney, especially if patients are hypertensive or proteinuric. However, angiotensin 2 (ANG2) levels permit a functional adaptation to a reduced renal mass in adults and is crucial for sustaining complete kidney development and maturation in children. A hormonal interference on ANG2 levels has been supposed in women. Consequently, at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Contrary to the belief that ACE inhibitors may lead to kidney damage, Simeoni M et al showed that anti-renin angiotensinaldosterone system drugs were renoprotective in patients with a solitary kidney. 23 As such, we considered the use of ACE inhibitors in our case, at an accordingly adjusted dose, but we ended up not doing so. Alongside the medical management of this child, the team concluded that watchful waiting for the need of surgical repair might be a safe path.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the belief that ACE inhibitors may lead to kidney damage, Simeoni M et al showed that anti-renin angiotensinaldosterone system drugs were renoprotective in patients with a solitary kidney. 23 As such, we considered the use of ACE inhibitors in our case, at an accordingly adjusted dose, but we ended up not doing so. Alongside the medical management of this child, the team concluded that watchful waiting for the need of surgical repair might be a safe path.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II is a potent vasoconstrictor, besides promoting sympathetic activation. It also induces proliferation of smooth muscle cells and increases glomerular and tubular expression of several growth factors, cytokines and chemokines, which can result in glomerular hypertrophy, sclerosis, tubulointerstitial inflammation, and fibrosis (7, 9, 20, 21). Angiotensin II is now recognized as a proinflammatory agent able to modulate immunologic and inflammatory responses in endothelial, renal tubular and smooth muscle cells, such as chemotaxis, proliferation and differentiation of monocytes into macrophages (22), whereas aldosterone, primarily promotes salt retention.…”
Section: Hypertension As a Risk Factormentioning
confidence: 99%
“…However, its degree of expression can influence progression of renal injury. Recently, Simeoni et al carried out a literature review assessing the effect of the drug in these patients (9). Despite the scarcity of related data, it was suggested that anti-RAAS agents also have a renoprotective effect in patients with a single kidney, with little evidence of serious adverse effects.…”
Section: High Blood Pressure Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothyroidism is a relatively silent condition due to the lack of clinical manifestations, and can be easily ignored. High incidence rate of chronic kidney disease in patients with cardiovascular disease results in increased mortality rate (7). There is a clear relation between chronic kidney disease, cardiovascular disease and hypothyroidism demonstrated by epidemiological studies (8).…”
Section: Introductionmentioning
confidence: 99%